SHORT-TERM OBSERVATION ON MARINE DEBRIS AT COASTAL AREAS OF TAKALAR DISTRICT AND MAKASSAR CITY, SOUTH SULAWESI-INDONESIA - Tahir, Akbar; Werorilangi, Shinta; Isman, Fajar Maulana; Zulkarnaen, Adi; Massinai, Arniati; Faizal, Ahmad (Jurnal Ilmu Kelautan SPERMONDE, 2018)
Marine debris is defined as material that is solid, persistent, manufactured or processed, and deliberately or not-deliberately left in the marine environment. Marine debris comes in many shapes and forms, ranging in size from microscopic microplastics to large vessels. Marine debris is a big and growing global problem, pose threats to marine life sustainability. Plastic is a major component of marine debris, and single-use packaging accounts for an increasing part of the global marine debris load. Research on marine debris was conducted on coastal areas and Small Island of South Sulawesi destined for local tourism, i.e., Karama beach, Bodia beach and Mandi beach (Galesong, Takalar District), Tanjung Bayang beach, Akkarena beach and Lae-lae island/also known as Bob beach (Makassar City). This research was aimed at identifying marine debris according to its types, size, and mass. Debris was collected in a 25 x 60 m transect with direction 30 m towards land and waters, respectively, with 3 replication transects at every location, whilst collections of debris were conducted during low and high tides. Current (direction and speed) and waves (incoming direction and height) were also measured as supporting parameters. Surrounding sampling location characteristics were also recorded. The result showed that Karama beach is found with highest total marine debris mass in Takalar (36.44 kg), whilst in Makassar, the Lae-lae island was found to be the highest with debris mass (43.22 kg). Plastic was predominant debris at all sampling locations with percentages of 62.7 – 86.6%. Lastly, the predominant size was macro-debris (25-100 cm).